PENGARUH SUPLEMENTASI PROBIOTIK YANG BERBEDA PADA AIR MINUM TERHADAP TOTAL LEUKOSIT DAN DIFERENSIAL LEUKOSIT BROILER - Mayhendra Putra Asmara, Purnama Edy Santosa, Siswanto, dan Sri Suharyati (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2019)
This study aimed to determine: 1) the total of leukocytes and differential leukocytes of broilers given different probiotics; 2) the best total of leukocytes and leukocyte differentials with the different probiotics. This research was carried out on January 10 2018 to February 9 2018. This research held at the farm and leukocyte analysis and differential leukocyte were carried out at the Lampung Veterinary Laboratory. The experimental design used completely randomized design with 3 replications with each test having 25 experimental units and 4 treatments (P0: drinking water without probiotics, P1: drinking water with probiotics A, P2: drinking water with probiotics B, and P3: drinking water with probiotics C). Treatment was given to broilers aged 7 days. Leukocytes and differential leukocytes were tested by WBC test. Observation data were analyzed with 5% and / or 1% level variance and continued with the Smallest Significant Difference test. The results of this study showed thesupplementation of probiotics in drinking water had significant effected (P <0.01) on the total of leukocytes and had a significant effect (P <0.05) on lymphocytes and neutrophils while not significant effected (P> 0.05) on basophils , eosinophils, and monocytes of broiler chicken. Keywords: Broiler chicken, Leukocyte, Differensial leukocytes, Probiotics